Increased risk and severity of unprovoked venous thromboembolism with clustering cardiovascular risk factors for atherosclerosis: Results of the REMOTEV registry. (1st February 2018) - Gaertner, S.; Cordeanu, E.-M.; Mirea, C.; Frantz, A.-S.; Auger, C.; Bilbault, P.; Ohlmann, P.; Schini-Kerth, V.; Stephan, D.
Abstract: Background: The role of cardiovascular risk factors (CVRF) for atherosclerosis in venous thromboembolic disease (VTE) is controversial. The aim of this study was to evaluate the impact of CVRF and their cumulative effects on the occurrence of unprovoked VTE, severity, recurrence and survival. Methods and results: This is a prospective cohort from the REMOTEV registry including all consecutively hospitalized patients for acute symptomatic VTE. From November 2013 to December 2016, 515 patients with 6 months follow-up (FU) were selected for the analysis. Events were classified as unprovoked or provoked VTE. In univariate analysis, hypertension (OR 1.44, [95% CI 1.01–2.06]), diabetes (OR 2.07, [95% CI: 1.25–3.55]) and age (OR 1.94, [95% CI: 1.31–2.88]) were significantly associated with the risk of unprovoked VTE. After adjustment, diabetes (OR 1.82, [95% CI: 1.07–3.18]) and age (OR 1.79, [95% CI: 1.15–2.8]) remained associated with the risk of unprovoked VTE. The proportion of unprovoked VTE increased significantly with the number of CVRF adjusted for thrombophilia (1 CVRF: OR 3 [95% CI: 1.44–6.52]) 2 CVRF: OR 4.33 [95% CI: 2.07–9.49] and ≥ 3 CVRF: OR 4.58 [95% CI: 2.27–9.7]). The severity of pulmonary embolism was significantly associated with CVRF clustering. There were more VTE recurrences and deaths during the 6 months of FU with cumulative CVRF. Conclusion: The risks of unprovoked VTE and PE severity are associated with clustering CVRF. The role of cumulative CVRF predominates rather than the specific burden of each of the CVRF in the risk of VTE occurrence. Highlights: Increased risk of unprovoked VTE with cardiovascular risk factors clustering. Pulmonary embolism severity increased with cumulative atherosclerotic risk factors. Increased VTE recurrence and mortality with cardiovascular risk factors burden. No thrombophilia impact on unprovoked VTE — cardiovascular risk factors association.